Compensatory growth in Nubian female goats in Sudan Effect on performance (A) - Yagoub, Yagoub Magboul; Babiker, Salih Ahmed (Journal of agricultural, environmental and veterinary sciences, 2024)
Two groups of female goat kids less than one year in age, Nubian ecotype (15 kids/ group) and of the same initial weight (16.5 kg/kid) were subjected to two dietary levels of energy for 105 days, the first group was offered the highest energy diet (11.5 Mj ME/kcl) while the second group was given the lowest dietary energy diet (8.5 Mj ME/kcl). Through this term of the experiment (105 days) kids of the second group were found just to maintain their weight. Then seven kids from the second group was offered the highest energy diet (11.5 MjME/kcl) to reach the final weight obtained by the first group, it spent 175 days to reach that weight.  These kids which were raised on the lowest dietary energy level (8.5 MjME/kg) were used to study the effect of compensatory growth on the performance of the female goat kids. Weekly, daily rate of gains and total dry matter intake were significantly (P< 0.001) lower in the compensating female goats than the first group.
Keywords: Compensatory Growth; Female Nubian Goats’ Performance